MENAPAKI JEJAK HADRAH FATTAHILLAH DI KARTASURA 1998-2019 - Putra, Hafizhan Pramanda; Fuadi, Moh Asif; Sucipto, Sucipto (Keraton: Journal of History Education and Culture, 2022)
This research discusses about the journey of local Hadrah called Hadrah Fatahillah from Kartasura. The scope of this research started from 1998-2019. The problems that will be discusses start from the history of its establishment, the dynamics of of the journey and the existence of Hadrah Fatahillah. Based on the problems, this research used history research method start with  theme or topic, source collection, source verification, interpretation of data and the last part is historiography. This study expalains the historical facts that focus on primary data, such as archives, photos, articles, interviews with the perpetrators and also the historicalo witnesses themselves and supported by relevant references and previous research. The result of this research bring out that development of Hadrah in Indonesia to smaller area such Kartasura. The establishment of Hadrah Fattahillah in Karatsura originated from the local tradition of berjanjen and terbangun pesisiran in Sedahromo, Kartasura environment. The estabilishment of Hadrah Fattahillah intend to preserve Islamic culture and grow sense of love to Rasulullah SAW with sholawat. The journey of Hadrah Fattahillah began with won the tournament of Islamic art in 1998-2019 then some of mambers out from Hadrah Fattahillah and force them to rebuild the group in 2004. Hadrah Fattahillah started to grown up in 2005 till 2014 and the declined guardly in 2015 till 2019.